KNOWLEDGE REGARDING THE INDICATIONS, CONTRAINDICATIONS AND ADVANTAGES OF CBCT EXAMINATIONS AMONG DENTISTS AND SPECIALISTS - George Stoica; Carina Balcoș; Mădălina Duceac (Covrig); Alexandru Nemțoi; Ana Elena Sîrghe; Adina Armencia; Roxana Mihaela Popescu; Bogdan Dobrovăț; Danisia Haba (Romanian Society of Oral Rehabilitation, 2023)
CBCT has proven to be a highly effective diagnostic tool for maxillofacial imaging and has a wide range of dental uses. Aim: the goal of this study was to assess dentists and specialits level of knowledge and attitudes regarding the indications, contraindications, and benefits of CBCT tests. Material and methods: In this cross-sectional study, the participants responded to online questionnaires that asked them about their experience using CBCT, its benefits and drawbacks, operational principles, and their reasons for recommending or not recommending CBCT. With SPSS 26.0, a statistical analysis was performed. Results: Dentists and prosthetists specialits consider that they have good knowledge regarding the use of CBCT, the same situation being recorded for those who have more than 20 years of work experience. 93.3% of dentists and all specialists recommended CBCT to patients, the trend being the same in terms of seniority where 75% of those with less than 5 years of experience and all doctors with more than 5 years of experience recommended CBCT to patients Most of the participating doctors attended training courses on the use of CBCT. The main reasons why CBCT is not recommended are because it is not necessary (40%), it is an expensive operation (26.7%). Most participants prefer to perform their own interpretation of the radiological examination, except for half of the dentists, prosthetists. Conclusion:The results of the study indicate a satisfactory level of knowledge and attitudes regarding the use of CBCT. Dentists and prosthodontists recommend the use of CBCT as a more frequent diagnostic method. Practitioners with more years of practice, are more reluctant to use this method of radiological evaluation frequently.